READERS’ KNOWLEDGE AND PURPOSE FOR SELF-ACTUALIZATION AFFECTING READING INTENTION FOR HOAX AMONG AVIATION SCHOOL ACADEMIA - Yune Andryani Pinem; Dyaz Varrel Effendi (Jurnal Manajemen Dirgantara, 2021)
Prior studies on knowledge and or reader purpose have been proven to lead readers’ attitudes. Emerging hoax news circulating social networking sites (SNSs) including among scholars has become a research concern recently. To determine the extent of knowledge and reading purpose on hoax about air transport subject among academia is the purpose of this study. Furthermore, it also measures the effect of those variables on reading intention. Using questionnaires, data is collected from students, instructors, teachers, and staff (n=100) from aviation school. Multivariate regression is applied toward two independent variables (readers’ knowledge and purpose) and one dependent variable (reading intention). Results of this study depicts simultaneously significant impact of readers’ knowledge and purpose of reading to readers’ intention to click on certain news.